Longitudinal antinuclear antibody titers in systemic lupus erythematosus and other rheumatic diseases - Littlejohn, Emily A.; Kong, Lingxuan; Wang, Lu; Somers, Emily C. (Frontiers in Medicine, 2024)
Antinuclear antibodies (ANAs) are a key feature of systemic lupus erythematosus (SLE) and marker of subclinical autoimmunity. Little is known about longitudinal ANA titers in individuals from the general population or in predicting clinical disease course in persons with rheumatic diseases. Methods: We performed an exploratory analysis from an academic health system between 1999-2020 to assess intra-individual variation in ANAs longitudinally in persons with SLE, other ANA-associated rheumatic diseases, and ANA+ controls without rheumatic disease. Results: Persons with SLE had a higher odds of positive ANA compared to those with other ANA-associated rheumatic diseases [OR 2.10, 95% CI (1.82, 2.43)] controlling for time and demographics (age, sex, race, ethnicity). Compared to ANA+ controls, the ANA titer strength was significantly higher for both the ANA-associated rheumatic disease (0.33 log units higher) and SLE groups (0.42 log units higher) controlling for demographics and time (p<0.001 for both). Over time from the first positive ANA, titer strength significantly decreased for all three groups, with average monthly decreases ranging between 0.001 to 0.004 log titer units (p ≤ 0.001 for all). Conclusions: Based on this analysis of electronic health data spanning two decades, ANA titers may be more dynamic than previously accepted in patients with SLE and ANA-associated rheumatic diseases, with average titers tending to be higher in early disease and decreasing over time.